Optimizing Employee Performance: Analysis of Determinants of Employee Performance - Sucipto, Hadi; Suaedi, Falih; Setijaningrum, Erna; Amiati, Mia (RSF Conference Series: Business, Management and Social Sciences, 2024)
In organizational contexts, human resources (HR) play a vital role in achieving synergy and organizational goals. Competent and dependable employees are essential for an organization’s success. Effective HR management ensures that employees are not only skilled but also aligned with the organization’s objectives. This study investigates the impact of personal character, HR competency, compensation, and work culture on employee performance. Using a quantitative approach, the research involved 80 employee prosecutors in East Java, selected through total sampling. Data collection relied on the Likert scale, and multiple linear regression was employed for analysis. Notably, compensation emerged as the dominant factor influencing employee performance, with positive and significant effects. Improving compensation practices can lead to enhanced employee performance.